2020
DOI: 10.56093/ijas.v90i4.102206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, heritability and correlation studies in soybean (Glycine max)

Abstract: Genetic variability parameters and correlation among 11 quantitative traits were studied in 219 soybean working collection during kharif 2014-15 at Bengaluru. Analysis of variance revealed significant differences among the 219 accessions for all the quantitative characters studied except for the seed size. Among the traits, number of clusters per pod exhibited highest estimate of phenotypic coefficient of variance (PCV) (37.04) and genotypic coefficient of variance (GCV) (36.94) followed by 100-seed weight (g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…2. These results are corroborating with earlier results of wide range of variation in soybean was reported by Jandong et al [13], Nayana and Fakrudin [14], Rahaman et al [15], Sahoo et al…”
Section: Analysis Of Variance (Anova)supporting
confidence: 93%
See 4 more Smart Citations
“…2. These results are corroborating with earlier results of wide range of variation in soybean was reported by Jandong et al [13], Nayana and Fakrudin [14], Rahaman et al [15], Sahoo et al…”
Section: Analysis Of Variance (Anova)supporting
confidence: 93%
“…Jandong et al [13] observed high value of PCV and GCV for plant height, number of leaves, number of pods and seed yield. Nayana and Fakrudin [14], reported high GCV for number of clusters/plant, 100-seed weight, number of branches/plant, plant height, number of pods/cluster and seed size. Sonkamble et al [19] observed high values of GCV and PCV for 100 seed weight, seed yield and harvest index.…”
Section: Coefficient Of Variationmentioning
confidence: 99%
See 3 more Smart Citations